Wakaf Basyari Pondok Modern Darussalam Gontor (PMDG) ‎Indonesia: Potensi dan Halangan Pelaksanaannya di ‎Malaysia: Basyari Waqf at Pondok Modern Darussalam Gontor (PMDG) ‎Indonesia: Potentials and Challenges of Its Implementation in ‎Malaysia - Hussin, Zul-kifli; Zabidi, Ainul Mardhiah; Saad, Shazalmi (RABBANICA - Journal of Revealed Knowledge, 2025)
Waqf is an Islamic financial instrument with great potential to address current and future of economic pressure. In reality, not all institutions can implement it and fully capitalize on its potential. One of the key reasons for this is that the waqf way of life and culture have not been instilled in children from a young age, resulting in a generation without a waqf-oriented mindset. Drawing from the experience of Pondok Modern Darussalam, Gontor [PMDG], it was developed from waqf funds by a generation of waqf-minded individuals. To date, this waqf fund has become a significant pillar in the management of education, medicine and plantations in Gontor. More importantly, the sustainability of waqf in Gontor is supported by one of the five main principles known as the five souls (panca jiwa), namely sincerity. From this principle, the concept of the basyari waqf was born. This article aims to highlight both the potential and obstacles in implementing Gontor’s basyari waqf model in Malaysia. To achieve this, a qualitative research design was employed, with data collected through document analysis, direct observation, and semi-structured interviews. The data was subsequently analyzed using content analysis. The study found that the Basyari Waqf has the potential to be successfully realised in Malaysia, provided that it is initiated by the highest authorities to instil a waqf mindset among employees. Obstacles to implementation can be overcome with careful planning and supporting documents certified by law. The study’s implications suggest that implementing the Basyari Waqf model can foster a culture of endowment and optimize the utilization of voluntary human resources. Additionally, it encourages policymakers to adopt this model as a reference in the development of the waqf system in Malaysia. Wakaf ialah instrumen kewangan Islam yang berpotensi besar dalam menangani tekanan ekonomi. Namun, pelaksanaannya terbatas kerana budaya berwakaf tidak dipupuk sejak kecil. Pondok Modern Darussalam Gontor (PMDG) membuktikan kejayaan wakaf apabila institusinya dibangunkan dan dibiayai oleh generasi berminda wakaf. Hingga kini, dana ini menjadi tunjang sektor pendidikan, perubatan dan perladangan, berasaskan prinsip ikhlas dalam Panca Jiwa yang melahirkan konsep wakaf basyari. Artikel ini bertujuan untuk mengetengahkan potensi dan halangan pelaksanaan wakaf basyari model PMDG di Malaysia. Bersesuaian dengan tujuan tersebut, reka bentuk kajian kualitatif digunakan dengan sokongan data daripada analisis dokumen, pemerhatian langsung, dan temu bual separa berstruktur. Seterusnya, data yang diperoleh dianalisis melalui kaedah analisis kandungan. Dapatan kajian mendapati bahawa wakaf basyari memiliki potensi untuk direalisasikan di Malaysia dengan syarat ia perlu dimulai oleh pihak tertinggi sehingga membentuk minda wakaf dalam kalangan pekerja. Halangan pelaksanaannya boleh diatasi jika dirancang dengan teliti berserta dokumen sokongan yang diperakui oleh undang-undang. Oleh itu, kajian ini mencadangkan agar institusi di Malaysia mencontohi model wakaf basyari PMDG dalam usaha membangunkan model wakaf basyari di Malaysia. Implikasi kajian menunjukkan bahawa penerapan model wakaf basyari berpotensi membudayakan amalan wakaf serta mengoptimumkan penggunaan sumber tenaga manusia secara sukarela. Selain itu, ia turut mendorong pembuat dasar untuk menjadikan model ini sebagai rujukan dalam pembangunan sistem wakaf di Malaysia.